Electrochemical, Energy, Exergy, and Exergoeconomic Analyses of Hybrid Photocatalytic Hydrogen Production Reactor for Cu-Cl Cycle - Ratlamwala, Tahir Abdul Hussain; Dincer, Ibrahim (Springer International Publishing Ag, 2018)
[Abstract Not Available]
7th International Exergy, Energy and Environmental Symposium (IEEES) -- APR 27-30, 2015 -- Univ Valenciennes, Valenciennes, FRANCE
Keywords: H-2 Evolution; Composite; Sulfide